Efficient CNV breakpoint analysis reveals unexpected structural complexity and correlation of dosage-sensitive genes with clinical severity in genomic disorders. - Zhang, Ling; Wang, Jingmin; Zhang, Cheng; Li, Dongxiao; Carvalho, Claudia M B; Ji, Haoran; Xiao, Jianqiu; Wu, Ye; Zhou, Weichen; Wang, Hongyan; Jin, Li; Luo, Yang; et al. (Hum Mol Genet, 2017)
Genomic disorders are the clinical conditions manifested by submicroscopic genomic rearrangements including copy number variants (CNVs). The CNVs can be identified by array-based comparative genomic hybridization (aCGH), the most commonly used technology for molecular diagnostics of genomic disorders. However, clinical aCGH only informs CNVs in the probe-interrogated regions. Neither orientational information nor the resulting genomic rearrangement structure is provided, which is a key to uncovering mutational and pathogenic mechanisms underlying genomic disorders. Long-range polymerase chain reaction (PCR) is a traditional approach to obtain CNV breakpoint junction, but this method is inefficient when challenged by structural complexity such as often found at the PLP1 locus in association with Pelizaeus-Merzbacher disease (PMD). Here we introduced 'capture and single-molecule real-time sequencing' (cap-SMRT-seq) and newly developed 'asymmetry linker-mediated nested PCR walking' (ALN-walking) for CNV breakpoint sequencing in 49 subjects with PMD-associated CNVs. Remarkably, 29 (94%) of the 31 CNV breakpoint junctions unobtainable by conventional long-range PCR were resolved by cap-SMRT-seq and ALN-walking. Notably, unexpected CNV complexities, including inter-chromosomal rearrangements that cannot be resolved by aCGH, were revealed by efficient breakpoint sequencing. These sequence-based structures of PMD-associated CNVs further support the role of DNA replicative mechanisms in CNV mutagenesis, and facilitate genotype-phenotype correlation studies. Intriguingly, the lengths of gained segments by CNVs are strongly correlated with clinical severity in PMD, potentially reflecting the functional contribution of other dosage-sensitive genes besides PLP1. Our study provides new efficient experimental approaches (especially ALN-walking) for CNV breakpoint sequencing and highlights their importance in uncovering CNV mutagenesis and pathogenesis in genomic disorders.
Keywords: Base Sequence; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Dosage; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genome, Human; Genomics; Humans; Male; Mutation; Pelizaeus-Merzbacher Disease; Sequence Analysis, DNA

CNV instability associated with DNA replication dynamics: evidence for replicative mechanisms in CNV mutagenesis. - Chen, Lu; Zhou, Weichen; Zhang, Cheng; Lupski, James R; Jin, Li; Zhang, Feng (Hum Mol Genet, 2015)
Copy number variation (CNV) in the human genome is of vital importance to human health and evolution of our species. However, much of the molecular basis of CNV mutagenesis remains to be elucidated. Considering the DNA replication model of 'fork stalling and template switching' for CNV formation, we hypothesized that replication fork progression could be important for CNV mutagenesis. However, molecular assays of replication fork progression at the genome level are technically challenging. Instead, we conducted an estimation of DNA replication dynamics, as the statistic R, using the readily available data of replication timing. Small R-values can reflect 'slowed' replication, which could result from less fork initiation, reduced fork speed or fork barriers. We generated genome-wide profiles of R in the genomes of human, mouse and Drosophila. Intriguingly, the CNV breakpoints in all three genomes showed significantly biased distributions toward the genomic regions with small R-values, suggesting potential replication stress-induced CNV instability. Notably, among the human CNVs with distinct breakpoint junction characteristics, the homology-mediated and VNTR-mediated CNVs contribute the most to the correlation between CNV instability and the statistic R, consistent with the recent findings in the C. elegans and yeast genomes of repeat-induced DNA replication error and consequent CNV formation. The statistic R may reflect both replication stress and the effect of local genome architecture on fork progression. Our concordant observations suggest an important role for DNA replicative mechanisms in CNV mutagenesis and genome instability.
Keywords: Animals; DNA Copy Number Variations; DNA Replication; Drosophila; Genome; Genomic Instability; Humans; Mice